Microbiome markers in HPV-positive and HPV-negative women of reproductive age with ASCUS and SIL determined by V4 region of 16S rRNA gene sequencing - Peremykina, Anastasiya; Cheranev, Valery; Krivoy, Andrey; Andreev, Alexander O.; Repinskaia, Zhanna; Asaturova, Aleksandra V.; Korostin, Dmitriy; Rebrikov, Denis; Bayramova, Gyuldana R. (Frontiers in Microbiology, 2024)
Human papilloma virus (HPV) is the most common sexually transmitted infection worldwide. Cervicovaginal microbiota plays an important role in HPV infection and is associated with the development of squamous intraepithelial lesions (SIL). The natural history of cervical cancer involves reversible changes in the cervical tissue from a normal state, in which no neoplastic changes are detected in the squamous epithelium, to varying states of cellular abnormalities that ultimately lead to cervical cancer. Low-grade SIL (LSIL), like another cytological category - atypical squamous cells of undetermined significance (ASCUS), may progress to high-grade SIL (HSIL) and invasive cervical cancer or may regress to a normal state. In this work, we studied cervical canal microbiome in 165 HPV-positive and HPV-negative women of a reproductive age with ASCUS (HPV(+) n = 29; HPV(-) n = 11), LSIL (HPV(+) n = 32; HPV(-) n = 25), HSIL (HPV(+) n = 46), and the control group with negative for intraepithelial lesion malignancy (NILM) (HPV(-) n = 22). HPV16 is the most prevalent HPV type. We haven’t found any differences between diversity in studied groups, but several genus (like Prevotella (p-value = 0,026), Gardnerella (p-value = 0,003), Fannyhessea (p-value = 0,024)) more often occurred in HSIL group compared by NILM or LSIL regardless of HPV. We have found statistically significant difference in occurrence or proportion of bacterial genus in studied groups. We also identified that increasing of the ratio of Lactobacillus iners or age of patient lead to higher chance to HSIL, while increasing of the ratio of Lactobacillus crispatus lead to higher chance to LSIL. Patients with a moderate dysbiosis equally often had either of three types of vaginal microbial communities (CST, Community State Type) with the prevalence of Lactobacillus crispatus (CST I), Lactobacillus gasseri (CST II), and Lactobacillus iners (CST III); whereas severe dysbiosis is linked with CST IV involving the microorganisms genera associated with bacterial vaginosis and aerobic vaginitis: Gardnerella, Fannyhessea, Dialister, Sneathia, Anaerococcus, Megasphaera, Prevotella, Finegoldia, Peptoniphilus, Porphyromonas, Parvimonas, and Streptococcus.